2017
DOI: 10.1007/978-3-319-52727-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Identifying DOS and DDOS Attack Origin: IP Traceback Methods Comparison and Evaluation for IoT

Abstract: Society is faced with the ever more prominent concerns of vulnerabilities including hacking and DoS or DDoS attacks when migrating to new paradigms such as Internet of Things (IoT). These attacks against computer systems result in economic losses for businesses, public organizations and privacy disclosures. The IoT presents a new soft surface for attack. Vulnerability is now found in a multitude of personal and private devices that previously lacked connectivity. The ability to trace back to an attack origin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Recently, Cusack et al [35] discussed and compared many IP traceback approaches based on some metrics such as storage requirements, processing overhead, bandwidth overhead, scalability, etc.…”
Section: Iot Dos/ddos Countermeasure Approachesmentioning
confidence: 99%
“…Recently, Cusack et al [35] discussed and compared many IP traceback approaches based on some metrics such as storage requirements, processing overhead, bandwidth overhead, scalability, etc.…”
Section: Iot Dos/ddos Countermeasure Approachesmentioning
confidence: 99%
“…The IoT security principle of availability has been also addressed in several studies which have suggested solutions to overcome the security challenges associated with it. These include the works of Maleh et al [49], Kumar et al [50], Kasinathan et al [51], and Cusack et al [52].…”
Section: Iot Security Principlesmentioning
confidence: 99%
“…The IP traceback problem is defined as identifying the actual source of any packet transmitted across the Internet [25]. Various approaches have been proposed [26], [27], and recent studies were focused especially on DDoS attacks using Internet of Things (IoT) devices [12]. Currently, there are six main categories of IP traceback methods [27]: link testing [28], messaging [29], marking [30], logging [31], overlay [32], and pattern analysis [33].…”
Section: Related Workmentioning
confidence: 99%
“…We expect that successful investigations enabled by our scheme will be a strong deterrent to attacks even if it is only partially deployed in the Tor network. IP traceback problems have been intensively studied, in particular for countering denialof-service (DoS) and distributed denial-of-service (DDoS) attacks [12]. However, to the best of our knowledge, in no papers, has means of detecting the actual attack source in the Tor network been discussed.…”
Section: Introductionmentioning
confidence: 99%